2011
DOI: 10.1007/s10165-010-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional disturbance of the stress-adaptation system in patients with scleroderma

Abstract: There have been several reports indicating the association between recent stress experiences and the onset or the exacerbation of rheumatic diseases, although few such reports exist in patients with scleroderma (SSc). The present study was performed to elucidate whether there were any functional disturbances in the neuro-endocrine-immune system as a homeostatic system upon stress in SSc patients. Various serum levels of stress-related hormones and cytokines were examined before and after a mental calculation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…While we can only speculate on the putative mechanisms justifying this association, we are traced back to earlier reports of the co-existence of phenylketonuriaassociated mental retardation and scleroderma [58]. Further, there are data suggesting that patients with SSc may have disturbances of the nervous system as represented by an impaired response to stress [59], the detection of central nervous system ischaemic vasculopathy at magnetic resonance imaging [60,61] and the changes in cerebrovascular reactivity [62].…”
Section: Discussionmentioning
confidence: 66%
“…While we can only speculate on the putative mechanisms justifying this association, we are traced back to earlier reports of the co-existence of phenylketonuriaassociated mental retardation and scleroderma [58]. Further, there are data suggesting that patients with SSc may have disturbances of the nervous system as represented by an impaired response to stress [59], the detection of central nervous system ischaemic vasculopathy at magnetic resonance imaging [60,61] and the changes in cerebrovascular reactivity [62].…”
Section: Discussionmentioning
confidence: 66%
“…There is also predominance of Th17 and Th2 cells with release of IL-17, IL-4 and IL-13 at sites of lymphocytic infiltration which contributes to ongoing fibrosis [252]. Basal levels of cortisol, androstenedione, DHEA-S and 17-hydroxyprogesterone in patients with SSc do not differ from healthy controls [253, 254]. Levels of DHEA are lower and of ACTH are higher in SSc patients [254].…”
Section: Role Of Local Steroidogenic Pathways In Inflammatory Disomentioning
confidence: 99%
“…They also have a diminished response to a stress test or hypoglycemia, i.e. their level of cortisol does not increase [253, 254]. Apparently, the HPA axis malfunctions in these patients.…”
Section: Role Of Local Steroidogenic Pathways In Inflammatory Disomentioning
confidence: 99%
“…There have been a number of reports suggesting the possible involvement of stress and/or the stress-adaptation system in the pathogenesis of rheumatoid arthritis and systemic lupus erythematosus (SLE) 39 40 . It has also been reported that the serum NE levels are significantly higher in SSc patients than in normal individuals 1 . In addition, the mental stress-induced serum NE levels are also higher in SSc patients than in normal individuals based on mental calculation stress tests, suggesting that SSc patients may have an impaired function of the neuro-endocrine-immune system due to stress 1 .…”
Section: Discussionmentioning
confidence: 88%
“…NE is also synthesized in the locus coeruleus and adrenal medulla. It is well known that emotional stress and cold stimulation increase the systemic and/or local NE levels 1 2 3 . NE binds to the adrenergic receptor (AR) in multiple organs, including the heart, lungs, brain and skin.…”
mentioning
confidence: 99%